The effect of bicarbonate of soda in reducing digestive disorders and death losses in feeder lambs. - Cox, R.F. (Kansas Agricultural Experiment Station, 2012)
Among a number of means tested in an effort to minimize digestive disorders and death losses in lambs caused by “over-eating disease” baking soda appeared to be effective to some extent. At the Garden City Branch Agricultural Experiment Station, two lots of lambs recently were put on feed to check this. This experiment was completed in March and a detailed report of the results appears in Table III of the Sheep Investigations section of this bulletin.
Keywords: Sheep; Bicarbonate; Digestive disorders